(untitled) (Texas Journal of Medical Science, 2022)
The main directions of pathogenetically substantiated treatment of AD, differentiated correction of concomitant pathology are described in detail. The external therapy of atopic skin lesions in children with the use of modern dermatological cosmetics is presented in particular detail.